The Discovery of a New Mimivirus Isolate in Association with Virophage-Transpoviron Elements in Brazil Highlights the Main Genomic and Evolutionary Features of This Tripartite System - Bruna Luiza de Azevedo; João Pessoa Araújo Júnior; Leila Sabrina Ullmann; Rodrigo Araújo Lima Rodrigues; Jônatas Santos Abrahão (Viruses, 2022)
Mimiviruses are giant viruses of amoeba that can be found in association with virophages. These satellite-like viruses are dependent on the mimivirus viral factory to replicate. Mimiviruses can also be associated with linear DNA molecules called transpovirons. Transpovirons and virophages are important drivers of giant virus evolution although they are still poorly studied elements. Here, we describe the isolation and genomic characterization of a mimivirus/virophage/transpoviron tripartite system from Brazil. We analyzed transmission electron microscopy images and performed genome sequencing and assembly, gene annotation, and phylogenetic analysis. Our data confirm the isolation of a lineage A mimivirus (1.2 Mb/1012 ORFs), called mimivirus argentum, and a sputnik virophage (18,880 bp/20 ORFs). We also detected a third sequence corresponding to a transpoviron from clade A (6365 bp/6 ORFs) that presents small terminal inverted repeats (77 nt). The main genomic features of mimivirus argentum and of its virophage/transpoviron elements corroborates with what is described for other known elements. This highlights that this triple genomic and biological interaction may be ancient and well-conserved. The results expand the basic knowledge about unique and little-known elements and pave the way to future studies that might contribute to a better understanding of this tripartite relationship.